The disease profile of poverty: morbidity and mortality in northern Uganda in the context of war, population displacement and HIV/AIDS - Accorsi, S.; Fabiani, M.; Nattabi, B.; Corrado, B.; Iriso, R.; Ayella, E.O.; Pido, B.; Onek, P.A.; Ogwang, M.; Declich, S. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2005)
The population of Gulu District (northern Uganda) has been severely incapacitated by war, epidemics and social disruption. This study is aimed at describing disease patterns and trends in this area through a retrospective analysis of discharge records for 155 205 in-patients of Lacor Hospital in the period 1992—2002. The burden of infectious diseases in childhood is overwhelming, with malaria accounting for the steepest increase in admissions. Admissions for war-related injuries and malnutrition fluctuated with the intensity of the war and the severity of famine. Emerging and re-emerging infections, such as HIV/AIDS, tuberculosis and Ebola, accounted for a heavy disease burden; however, there has been a trend for admissions related to HIV/AIDS and tuberculosis to decrease since the implementation of communitybased services. Vulnerable groups (infants, children and women) accounted for 79.8% of admissions. Long-term war, population displacement, the collapse of social structures and the breakdown of the health system place people at a much greater risk of persistent, emerging and re-emerging infectious diseases, malnutrition and warrelated injuries, shaping the ‘disease profile of poverty’. Most of the disease burden results from infectious diseases of childhood, whose occurrence could be dramatically reduced by low-cost and effective preventive and curative interventions.
Keywords: Disease burden; Poverty; War; Population displacement; Epidemics; Uganda